2020
DOI: 10.1371/journal.pone.0232750
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum and abscisic acid coregulate chlorophyll production of seedling in switchgrass

Abstract: The rare earth element lanthanum (La) has been proven to be beneficial for plant growth with a low concentration, and abscisic acid (ABA) which is a plant hormone also can regulate plant growth. In the present study, we investigated the germination and seedling growth of switchgrass (Panicum virgatum L.) under La (10 μM), ABA (10 μM) and La + ABA treatments. The results showed that La, ABA and La + ABA treatments could not significantly affect the germination and shoot length as compared to the control (P>0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Compared to our UV-vis spectrum, these two peaks were blue-shifted by 53 and 65 nm, respectively. Indeed, our electronic absorption spectrum of MgCA was consistent with the previous calculations (Chen et al, 2003;He et al, 2020).…”
Section: Electronic Absorption Spectrumsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to our UV-vis spectrum, these two peaks were blue-shifted by 53 and 65 nm, respectively. Indeed, our electronic absorption spectrum of MgCA was consistent with the previous calculations (Chen et al, 2003;He et al, 2020).…”
Section: Electronic Absorption Spectrumsupporting
confidence: 92%
“…In rape (Brassica napus L.), the treatments with CeCl 3 and Nd (NO 3 ) 3 increased the chlorophyll content by 9-40% (Jie and Yu, 1985). Our previous work showed that treatment with La increased the chlorophyll content of switchgrass (Panicum virgatum L.) (He et al, 2020). Shen et al (1999) found that Abbreviations: La, lanthanum; Ce, cerium; Tb, Terbium; REEs, rare earth elements; LREE, light rare earth elements; HREE, heavy rare earth elements; CME, clathrin-mediated endocytosis; AGPs, arabinogalactan proteins; FW, fresh weight; TTC, triphenyl tetrazolium chloride; MgCA, Mg-chlorophyll a; MgCB, Mg-chlorophyll b; DFT, density functional theory; SDD, Stuttgart-Dresden; PCM, polarizable continuum model; SCRF, self-consistent reaction field; TDDFT, timedependent density functional theory.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of this paper, the earlier database (Agathokleous et al 2020b) was extended by adding 121 dose responses of chlorophylls to The rise and fall of photosynthesis: hormetic dose response in plants 1 3 22 stresses, mined from 25 published studies (of which 67% were published in 2020) with 24 species of higher plants, including tree and other perennial plants (Table S1). The 22 stresses included herbicides (Liu et al 2019;Meseldžija et al 2020), human and veterinary antibiotics (Guo et al 2020;Liu et al 2020a), metallic elements (Seth et al 2008;Tang et al 2009;Jia et al 2015;Apodaca et al 2017;Wu et al 2018;Li et al 2020a;Małkowski et al 2020;Mo et al 2020;Yang et al 2020), micro/nano-plastics (Dong et al 2020;Li et al 2020c;Lian et al 2020;Pignattelli et al 2020), and various other types (Mostofa et al 2015;Wang et al 2016;Soliman et al 2019;Kutty et al 2020;He et al 2020;Gohari et al 2020b, a;Trejo-Téllez et al 2020). More than half (57.0%) of the new dose responses were statistically significant compared with the control group (typically a zero dose of the same stressor), according to the original analysis (many of them did not report statistics).…”
Section: Analysis Chlorophylls In Higher Plantsmentioning
confidence: 99%
“…ABA is associated with changes in chlorophyll content. ABA‐mediated regulation of chlorophyll biosynthesis and degradation pathways can impact chlorophyll levels in leaves (He et al., 2020; Wang et al., 2018). However, there were no significant differences in ABA and chlorophyll contents between control and ApE‐treated plants irrigated with 0.6 mM Pi.…”
Section: Discussionmentioning
confidence: 99%